An evaluation of the roles of CHE and the SETAs in the accreditation of NQF Level 5 learning programmes - Nxumalo, Edmund Linduyise (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPA (School of Public Management and Planning))--University of Stellenbosch, 2009.